1986
DOI: 10.1128/jvi.60.1.224-229.1986
|View full text |Cite
|
Sign up to set email alerts
|

Complete Sequence and Enhancer Function of the Homologous DNA Regions of Autographa californica Nuclear Polyhedrosis Virus

Abstract: The nucleotide sequence of the five regions of homologous DNA in the genome of Autographa californica nuclear polyhedrosis virus DNA was determined. The homology of repeated sequences within a region was 65 to 87%, and the consensus sequences for each region were 88% homologous to each other. Sequences proximal to the EcoRI sites were most conserved, while the distal sequences were least conserved. The EcoRI sites formed the core of a 28-base-pair imperfect inverted repeat. All homologous regions functioned as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(60 citation statements)
references
References 35 publications
0
59
0
1
Order By: Relevance
“…Most baculoviral genomes contain homologous repeat sequences (hrs), which typically consist of a few repeated sequences with imperfect palindromes that are interspersed within the genome. The hrs of different baculoviruses are highly variable (Ferrelli et al 2012), and previous studies have suggested that hrs can act as origins of DNA replication and enhancers of gene expression (Guarino et al 1986;Kool et al 1993;Rodems and Friesen 1995;Theilmann and Stewart 1992). A total of 13 hrs were identified in the CyunNPV genome ( Fig.…”
Section: Repeat Regionsmentioning
confidence: 99%
“…Most baculoviral genomes contain homologous repeat sequences (hrs), which typically consist of a few repeated sequences with imperfect palindromes that are interspersed within the genome. The hrs of different baculoviruses are highly variable (Ferrelli et al 2012), and previous studies have suggested that hrs can act as origins of DNA replication and enhancers of gene expression (Guarino et al 1986;Kool et al 1993;Rodems and Friesen 1995;Theilmann and Stewart 1992). A total of 13 hrs were identified in the CyunNPV genome ( Fig.…”
Section: Repeat Regionsmentioning
confidence: 99%
“…pAcIE1, pIE1HRGalT, pIE1HRST6, and pIE1Hygro are immediate early expression plasmids that encode AcMNPV IE1 (Guarino and Summers, 1987), bovine ␀1,4-galactosyltransferase (␀1,4GalT; Shaper et al, 1986), rat ␣2,6-sialyltransferase (␣2,6SiaT; Weinstein et al, 1987), or hygromycin phosphotransferase (Yates et al, 1985), respectively, under the transcriptional control of the AcMNPV ie1 promoter (Guarino and Summers, 1987) and hr5 enhancer (Guarino et al, 1986). The construction of each of these plasmids has been described previously (Hollister and Jarvis, 2000;Hollister et al, 1998).…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…Each hr contains from two to eight 24-bp imperfect palindromes with naturally occurring EcoRI sites at their core. The hrs function as enhancers of early viral gene expression (11,12). The baculovirus transactivator IE1 binds to DNA sequences within the enhancer regions (9,10).…”
mentioning
confidence: 99%